Utilization of Sulfur Material from Ijen Crater Banyuwangi as Interior Room Clock Accessory - Vindy Reychani Iktarishafa; Sunarmi Sunarmi; Sumarno Sumarno (Dinasti International Journal of Education Management And Social Science, 2025)
Ijen Volcano is an area of active volcanic activity located in East Java Province, on the border of Banyuwangi and Bondowoso Regencies. The abundance of sulfur encourages sulfur mining activities on Mount Ijen. This can provide both benefits and impacts on the community's economy and the environment. Sulfur in the Ijen Crater must continue to be mined so that the spread of gas can be reduced and does not endanger visitors and miners who climb Mount Ijen. Therefore, it is necessary to develop the utilization of sulfur as a functional product. The method used in this research is design thinking, which includes five stages in the process of creating work, namely Empathize, Define, Ideation, Prototype, and Test. The result of the development of sulfur utilization is as an interior accessory for a room clock that functions as a timepiece, beautifies the room, has drawers to store items, and helps reduce the presence of mosquitoes in a room that is not too large. The conclusion of this research shows that further research is needed regarding the effectiveness of sulfur in repelling mosquitoes in more detail. This interior accessory in the form of a room clock plays a role in helping to increase the income of sulfur miners and support the stability of nature conservation through the development of sulfur utilization as an interior accessory.